Odpowiedź :
-17 + 15 = -(17 - 15) = -2
-11 + 15 = 15 - 11 = 4
-6 + 15 = 15 - 6 = 9
-19 + 15 = -(19 - 15) = -4
-15 + 15 = 15 - 15 = 0
-80 + 15 = -(80 - 15) = -65
-50 + (-100) = -(50 + 100) = -150
-75 + (-100) = -(75 + 100) = -175
125 + (-100) = 125 - 100 = 25
-17 + (-100) = -(17 + 100) = -117
53 + (-100) = 53 - 100 = -(100 - 53) = -47
457 + (-100) = 457 - 100 = 357
Odpowiedź:
-17 + 15 = -(17 - 15) = - 2
-11 + 15 = 15 - 11 = 4
-6 + 15 = 15 - 6 = 9
-19 + 15 = -(19 - 15) = - 4
-15 + 15 = 15 - 15 = 0
-80 + 15 = -(80 - 15) = - 65
-50 + (-100) = -(50 + 100) = - 150
-75 + (-100) = -(75 + 100) = - 175
125 + (-100) = 125 - 100 = 25
-17 + (-100) = -(17 + 100) = - 117
53 + (-100) = 53 - 100 = -(100 - 53) = - 47
457 + (-100) = 457 - 100 = 357
Szczegółowe wyjaśnienie: